The Tasks of Individuals Practicing Human Factors and Ergonomics - Rabiul, Ahasan; Saiful Bahri, Mohamed (2016)
Human factors professionals and ergonomists are believed to be autonomous scientists since their area of interests cover wide range of knowledge, skills and experiences (www.usernomics.com/humanfactors. html). HFs/E is a multidisciplinary field of interests that involve psychology, social engineering, system design, economics, and ethnography. Professionals often used the term HFs experts in the US and Canada, and in Europe they are called as ergonomists. Generally, HFs/E deals with the subject matters of human-technology and environmental relationships that co-exist in independent domains mainly on behavioural, cognitive, and physical sciences. In many countries, HFs/E discipline co-exists between health, safety, and productivity combining various components that affect workers’ wellbeing at their workplaces. In Asia, Africa and Latin America, it is difficult to determine who is who in the HFs/E profession [1-2]. It is because HFs/E uses an interdisciplinary approach to evaluate parameters of a worker and his/her work environment to improve safety, health, efficiency, and robustness of work systems [3]. HFs/E concepts could inevitably be applied anywhere, however. HFs/E is about how people interact with the system to get information and then interpret the information they gathered to make decisions (manmachine- environment system). In figure 1, we see a person using a system, for example, and we also see how the system could adapt itself to a new situation over time.